Relative gene expression analysis of β-casein gene and its transcription regulatory genes in primary buffalo mammary epithelial cells of Surti and Jaffarabadi buffaloes - PANDYA, GAURAV; RAMANI, UMED; JANMEDA, MAMTA; TYAGI, KULDEEP; BRAHMKSHTRI, BALKRUSHNA; KHARADI, VISHNU (The Indian Journal of Animal Sciences, 2018)
The present study was designed to estimate the relative gene expression of major genes responsible for β-casein and its transcription regulation during early lactation cycle in Surti and Jaffarabadi buffaloes. Ten buffaloes of each breed maintained at Livestock Research Station, Navsari and Cattle Breeding Farm, Junagadh, respectively were selected for the study. The RNA was extracted from noninvasively isolated primary buffalo mammary epithelial cells (pBMEC) obtained using antibody mediated magnetic separation method from milk samples collected at day 15 and 60 postpartum (pp). Primers used for amplification of β-casein gene (CSN2) and its transcription regulatory genes were bovine specific. The mean relative expressions of C/EBPβ, RUNX2 and STAT5A genes were significantly higher in Jaffarabadi buffaloes as compared to Surti buffaloes at day 15 pp. However, between breed differences in the mean relative expressions of C/EBPβ, RUNX2 and STAT5A genes were not observed at 60 days pp. The relative expressions of CSN2 and YY1 genes did not differ significantly within or between breeds. The mean relative expression of KRT8 gene was almost comparable among all the groups under present study. Thus, only β- casein transcription regulatory genes C/EBPβ, RUNX2 and STAT5A amongst all studied genes showed significant between breed variability at day 15 pp, however this variability too got subsided as lactation stage advanced to day 60 pp.